Untargeted metabolomics reveals enhanced antioxidant capacity and key bioactive components of Gougunao No. 2 black tea - Lu, Junjie; Ai, Jiahao; Wang, Cong; Jiang, Junfeng; Zhou, Xinjie; Guo, Yongfa; Zhong, Zhuangzi; Zhou, Jie; Wu, Yang; Liu, Ding-kun; Sun, Huimin (Frontiers in Nutrition, 2026)
IntroductionCultivar background may influence antioxidant-related non-volatile metabolite composition of black tea even under identical manufacturing conditions, but the compositional basis and its relationship to assay-specific antioxidant readouts remain unclear.MethodsWe conducted a controlled comparison of black teas produced from Gougunao No. 2 (G2R) and the traditional Gougunao group small-leaf cultivar (BDZ) using the same processing protocol. Untargeted metabolomics was performed using ultra-high-performance liquid chromatography coupled to high-resolution mass spectrometry (UPLC-HRMS) in positive and negative ion modes, followed by differential-metabolite analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment based on the differential-metabolite list. Antioxidant-related properties were evaluated using ferric-reducing antioxidant power (FRAP), hydroxyl-radical (·OH) scavenging, ABTS radical-cation (ABTS•+) scavenging, and DPPH radical (DPPH•) scavenging, together with total phenolic content and total flavonoid content.ResultsMultivariate analyses showed clear cultivar-dependent separation of global metabolite fingerprints. Positive-ion data highlighted enrichment of amino-acid-related pathways, consistent with higher abundance of 10 annotated amino acids in G2R, whereas negative-ion data emphasized secondary-metabolism pathways centered on flavonoid and phenylpropanoid biosynthesis, accompanied by cultivar-dependent phenolic/flavonoid-related metabolic features. Functionally, G2R exhibited higher FRAP and stronger ·OH scavenging activity than BDZ, together with 10–30% higher total phenolics and total flavonoids, while ABTS•+ showed only a small, non-significant difference and DPPH• activities were comparable between cultivars.ConclusionUnder the tested conditions, cultivar background is associated with coordinated amino-acid- and phenolic/flavonoid-related metabolic differences and with assay-specific antioxidant indices, suggesting that integrated metabolomics-antioxidant profiling may be useful for quality-oriented cultivar evaluation within the scope of this two-cultivar study.